2018
DOI: 10.1101/450155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid embryonic cell cycles defer the establishment of heterochromatin by Eggless/SetDB1 inDrosophila

Abstract: 5 6 7Rapid embryonic cell cycles defer the establishment of heterochromatin by Eggless/SetDB1 in Drosophila.Acquisition of chromatin modifications during embryogenesis distinguishes different regions of an initially 11 naïve genome. In many organisms, repetitive DNA is packaged into constitutive heterochromatin that is 12 marked by di/tri methylation of histone H3K9 and the associated protein HP1a. These modifications enforce 13 the unique epigenetic properties of heterochromatin. However, in the early Drosoph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Specifically, the length of interphase limits the access of Eggless to chromatin, leading to insufficient Eggless activity on the chromatin and failure in heterochromatic foci formation. However, as cell cycle lengthens at the MBT stage, the effect of Eggless becomes sufficient to establish and maintain heterochromatic foci . This mechanism supports the hypothesis that cell cycle length could regulate the epigenome by controlling the time available for establishing/maintaining epigenetic marks.…”
Section: Potential Molecular Consequences Of Rapid Cell Cyclesupporting
confidence: 71%
See 1 more Smart Citation
“…Specifically, the length of interphase limits the access of Eggless to chromatin, leading to insufficient Eggless activity on the chromatin and failure in heterochromatic foci formation. However, as cell cycle lengthens at the MBT stage, the effect of Eggless becomes sufficient to establish and maintain heterochromatic foci . This mechanism supports the hypothesis that cell cycle length could regulate the epigenome by controlling the time available for establishing/maintaining epigenetic marks.…”
Section: Potential Molecular Consequences Of Rapid Cell Cyclesupporting
confidence: 71%
“…Seller et al . found that Eggless, the Drosophila H3K9 methyltransferase, mediates this process. Specifically, the length of interphase limits the access of Eggless to chromatin, leading to insufficient Eggless activity on the chromatin and failure in heterochromatic foci formation.…”
Section: Potential Molecular Consequences Of Rapid Cell Cyclementioning
confidence: 98%
“…Upon binding to the GFP‐tagged POI, GrabFPs have been shown to relocalize the GFP‐tagged POI from the endogenous localization domain to a novel, ectopic location (Figure f). In a similar way, a GFP nanobody fused to a lipid droplet‐associated scaffold has been successfully employed to relocalize GFP‐tagged nuclear proteins to lipid droplets to block their function (JabbaTrap, Seller, Cho, & O'Farrell, , Figure 1g).…”
Section: Overview Of Protein Binder Applications In Developmental Biomentioning
confidence: 99%
“…Recently, tools that re‐localize GFP‐tagged POIs to specific intracellular compartments in developing organisms have been reported (GrabFP, Harmansa et al, ; JabbaTrap, Seller et al, ). In both cases, the GFP nanobody has been fused to a protein scaffold with biased subcellular localization (plasma membrane, lipid droplets).…”
Section: Protein Relocalizationmentioning
confidence: 99%
See 1 more Smart Citation